Anti-Lock Breaking System Pada Krl Commuter Line Jabodetabek Sebagai Penunjang Keselamatan Mengunakan Fuzzy Inference System - Nurdin, Sam Ali; Bintoro, Ketut Bayu Yogha (JISA(Jurnal Informatika dan Sains), 2018)
The public transportation model which is currently widely used by people who live in Jakarta, Bogor, Depok, Tangerang and Bekasi (JABODETABEK) is the Commuter-Line Electric Train (KRL). According to online media sources(http://Kompas.com 2 December 2015), currently, the JABODETABEK Commuter-Line KRL can carry 900,000 passengers every day. Anti Lock Braking System (ABS) is a braking system that maintains the position of the wheels and the road to prevent tire/wheel slip. Anti Lock Braking System was first used or applied to aircraft. Vehicles that are not equipped with the Anti-lock Braking System must be updated. The driver makes optimal braking to prevent slip between the wheels and the road or rail so that the vehicle stops perfectly. In this paper, we will use fuzzy inference logic to support an Anti-lock Braking System (ABS). Fuzzy inference is a logical method because when determining variables in the fuzzy method, the variable must have an International Standard (SI).